Axiological elements of information systems oriented professional management decision as holder (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
In this article a paradigmatic version to decision makers at the administrative level based on the axiological elements of information systems is proposed. Which was developed in three stages beginning in investigating the main features of systems to support decision making, followed in a second step, the determination of the elements considered by management professionals regarding the decision-making process ethical through technology, to finally develop a systematic reflection of the axiological aspects of the use of information systems based on the significance levels of the elements involved in using these in making ethical decisions from the perspective of middle managers and senior Venamcham1 affiliated companies participating in the program RSE2 robust information systems; concluding that the professional administrative area as decision maker, direct or indirect user information systems, has joint responsibility with the computer field staff to be aware and take action regarding abuse of information technology in the areas of work within their organizations, including the proper discharge of its role as a vital human resource information systems that are used in organizations, and beyond is a member of a society.
Keywords: systems; axiological elements; making ethical decisions